Bibliometric Analysis of High School Keyword Using VOSviewer Indexed by Google Scholar - Dwi Novia Al Husaeni; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2023)
Schools are institutions designed for the learning process. The school level is divided into basic education, secondary education, and higher education. The purpose of the school is to develop the potential of students. The purpose of this research is to combine mapping analysis with the VOSviewer application. In addition to VOSviewer, Publish or Perish was also carried out in this study. The keyword used is